A Critical Review of Lakshmi Raj Sharma’s "We Should Not All Be Feminists" - Sharma, Tulna (Journal of Educational Research and Policies, 2026)
Lakshmi Raj Sharma’s novel We Should Not All Be Feminists (2024) is a satirical and ironic exploration of themes like love, spirituality, and gender empowerment while critiquing what the author calls "fake feminism. " Through a complex narrative, the novel juxtaposes Eastern and Western values, unraveling issues such as the breakdown of marriage, corruption of character, and the exploitation of feminism for personal and social gain. The story follows Emilia and Clarissa, two women who arrive in India to promote feminist ideas but end up highlighting the negative side of feminism that damages relationships and traditional values. The novel also addresses broader social issues like casteism, conversion, and the challenges faced by Indian women under societal pressures. With its humor, irony, and pathos, the narrative weaves a vivid portrayal of cross - cultural encounters, exposing the materialistic and superficial aspects of empowerment as understood by different characters.